29. CHROMOSOMAL COPY NUMBER ANALYSIS OF CHORIONIC VILLUS FROM SPONTANEOUS ABORTION BY NEXT GENERATION SEQUENCING. (August 2019) - Tamura, Y.; Santo, M.; Araki, Y.; Matsubayashi, H.; Takaya, Y.; Doshida, M.; Sakaguchi, K.; Yamaguchi, K.; Mizuta, S.; Kim, N.; Okuno, K.; Kitaya, K.; et al.
Abstract : Introduction: Chromosomal abnormalities are the most common reason for spontaneous abortion. Conventional cytogenetic analysis by G-banded karyotyping is generally performed for chromosomal analysis, but it has a problem with low-resolution, and is needed long term cell culture and enough experience for diagnosis. More recently, next generation sequencing has been introducing and improving for chromosomal analysis as an accurate, high resolution and throughput method. In this study we aimed to compare the consistency between conventional G-banding and NGS-based chromosomal copy number analysis for chorionic villus from spontaneous abortion. In addition, the frequency of each chromosomal aneuploidy was evaluated. Materials and methods: From February, 2018, to April, 2018, chromosomal analysis for 7 chorionic villus samples from spontaneous abortions (from 7 to 9 weeks) were carried out both conventional G-banding and NGS (VeriSeq-PGS, Illumia). The frequency of each chromosomal aneuploidy was investigated for 110 cases from February, 2018 to December, 2018. Results: NGS was able to analyze all 7 cases, but G-banding was able to detect 6 cases, and one case was cell growth failure. In 6 cases analyzed by G-banding, the results of 5 cases were consistent with the results of NGS, but one case suspected maternal cell contamination. Among 7 cases analyzed by the NGS, 2 cases were normal male karyotype (46, XY) and 5 cases were autosomal trisomy, implying that there were no cases suspected of maternal cell contamination. Among 110 cases, chorionic villus was not observed under microscope from 18 samples, NGS result was obtained from 92 cases. Seventy-one cases were found to have abnormal chromosomes (71/92, 77.2%), and 21 cases were normal karyotype (21/92, 22.8%). Aneuploidy of chromosome 22 (21.8%), chromosome 16 (17.9), chromosome 15 (11.9%), chromosome 21 (10.3%) and Chromosome X (10.3%) were more frequently, consistent with previous report. Conclusions: Chromosome analysis using NGS not only obtained comparable results to conventional G-banding, but also is able to analyze more accurately and quickly.